IMPLEMENTASI ZAKAT PRODUKTIF UNTUK PEMBERDAYAAN MUSTAHIK - Muhamartha, Dimas Putramanda; Anggraini, Ika Khusnia (Islamic Economics and finance in Focus, 2023)
Almsgiving or zakat has enormous potential in Indonesia. In 2019, the collected zakat funds in Indonesia amounted to approximately IDR 5.7 trillion. A number of these funds were distributed in 5 fields such as economy, education, healthcare, da'wah, and social humanity. From the results of zakat funds collection in Indonesia in 2019, 13.53% was distributed to the economic sector. It causes distribution in the economic sector to rank 4th. Besides, the goal of productive zakat is difficult to achieve because most of the zakat funds in Indonesia are distributed to the social humanitarian sector which is short-term assistance and is charitable. Therefore, this study aimed to see how the implementation and influence of productive zakat in efforts to empower micro-recipients of zakat mustahik. This study used the Lapak Berkah Program of LAZ Inisiatif Zakat Indonesia East Java as a research object. The results showed that the implementation of productive zakat through the Lapak Berkah Program influences efforts to empower mustahik. It can be seen from the existence of business development, the implementation of Islamic business ethics, and the ability to pay ZIS from mustahik through the Lapak Berkah Program.